Periostin as a Biomarker of Bronchial Asthma - Natalia V. Shakhova ("Paediatrician" Publishers LLC, 2020)
Immune inflammation regulated by CD4+ cells (T cells type 2) is integral to the pathogenesis of most cases of bronchial asthma (BA). However, not all mechanisms of chronic inflammation in BA are studied well enough. More recently the role of periostin (extracellular matrix protein) in development of eosinophilic inflammation and airway remodeling at BA has been revealed. The effect of periostin on BA course and development can be confirmed by its high expression in bronchial epithelium of patients with BA. This review shows current data on periostin structure and synthesis, correlation between periostin and BA course and development and pulmonary function test. Special attention is given to the periostin role in BA in children.